DEVELOPMENT OF MATERIALS CONFECTION DOCUMENTS ON COMBINED ELEMENT CLOTHING MODELS - Abdujabborova D. A.; Bazarbayeva G. G.; Kabilova D. S. (International Journal of Innovations in Engineering Research and Technology, 2023)
This article developed a structural model of the process of confecting materials into combined element sewing objects. The stages of the formation of a dress model confection card are indicated.